Taxonomy and Phylogeny of Two Spirotrichean Ciliates (Alveolata, Protista, and Ciliophora) From a Plateau Saline–Alkaline Lake in Tibet, China, Including Description of a New Species - Kouser, Farzana; Song, Wenya; Jiang, Limin; Zhuang, Wenbao; Wang, Congcong; Wu, Tong; Hu, Xiaozhong (Frontiers in Marine Science, 2022)
There are few researches concerning ciliates from “extreme” environments such as plateau salt lakes; nevertheless, such a faunistic survey is of great significance for understanding the diversity and biogeography of these microeukaryotes. In this study, two ciliates, namely, Hemiurosomoida tibetensis sp. nov. and Euplotes euryhalinusValbonesi and Luporini, 1990, isolated from Kyêbxang Co, a Tibet Plateau saline-alkaline lake, China, were investigated based on observations of live and silver-stained specimens, and 18S rDNA sequences were analyzed. The new species can be characterized by having a size of 60–95 × 20–40 μm in vivo, an elongate elliptical body, colorless cortical granules mainly grouped around cirri and dorsal bristles, about 21 adoral membranelles, 20 cirri on each marginal row, and two macronuclear nodules and two micronuclei. The Chinese population of E. euryhalinus corresponds well with the original one. Phylogenetic analyses show that Hemiurosomoida is non-monophyletic, H. tibetensis sp. nov. has a closer relationship with H. longa within this genus, and that Euplotes euryhalinus presents a wide geographic distribution. This study first reveals the ciliature, morphogenesis, and rRNA gene sequence data for H. tibetensis sp. nov. and the Chinese population of E. euryhalinus, which thus increases our knowledge about the diversity of ciliates at high altitudes.